'Re la Tsoantso' ('Father of the Pictures'): Joseph Denfield's Photography, 1944-1965 - Mnyaka, Phindezwa (Kronos: Southern African Histories, 2017)
This article explores the photographic work of Joseph Denfield, a medical doctor who rose to prominence as an amateur photographer and public intellectual in South Africa in the late 1950s and early 1960s. lt focuses on the manner in which and the extent to which Denfield participated in regional visual economies at different points in his career in order to establish his contribution towards visual histories in Southern Africa. Denfield experimented with various photographic genres, from ethnographic to pictorial work, which was widely circulated in salon exhibitions. Through a close reading of his photographs and writings relating in successive phases to his work in Northern Nigeria, Basutoland and East London, the article seeks to explore the wider frames of colonial photographic practice and their implications for creating alternative histories. Related to this is a reading of his photographs that he took at different stages against one another to figure out their shared visual grammar. This helps to deepen understandings around various genres of photography and to ask questions not simply about what historical photographs represent, but to interrogate how and why photographers did what they did.